TEM-EELS study of compressed graphite phase in high-pressure and high-temperature treated neutron-irradiated graphite - Yuta Ohsawa; Yohei K. Sato; Tomoya Saito; Masami Terauchi; Takashi Kitazume; Takumi Tokunaga; Yuji Higo; Keisuke Niwase; Masahito Niibe; Shin-ichi Honda (Carbon Trends)
The creation of new carbon materials has been attempted by treating neutron-irradiated graphite at high pressure and high temperature (HPHT) conditions. Recently, the formation of the compressed graphite (CG) with a (0002) plane distance of 3.2 Å, which is narrower than that of the graphite with a plane distance of 3.4 Å, was reported in the neutron-irradiated graphite processed under an HPHT condition. It is not clear what electronic structure, properties, and formation mechanism of the CG phase. In this study, electron energy-loss spectroscopy using a transmission electron microscope was applied to elucidate the electronic structure of the CG phase in the neutron-irradiated graphite sample with the HPHT treatment. The atomic layer distance of 3.2 Å for the CG phase was confirmed by an electron diffraction pattern. Dark-field images of 0002 spots of the CG phase showed the spatial distribution of the CG phase in the specimen. The electron energy-loss spectrum of the C K-edge of the CG showed a decrease in π* and σ* peak intensities, and the onset of the σ* peak shifted to the lower energy side compared with those of graphite. A first-principles calculation suggested that the electronic structure of graphite with the interlayer bond relating to the interstitial atoms and lattice vacancies should be reasonable for the electronic structure of the CG examined. Thus, the interlayer bonds formed by the interstitial atoms and the lattice vacancies introduced by neutron irradiation should contribute to the formation of the CG phase.